Human Rights in the Digital Age: Opportunities and Constraints. (3rd April 2017) - Monshipouri, Mahmood
Abstract : This article seeks to demonstrate the ways in which the growing digital diffusion of ideas and visions can help shape the political and social landscape at the local, national, regional, and global levels. While the context is varied, from the Occupy Wall Street movement to the Arab Spring to other social movements across the world, it is fair to argue that the new technologies have precipitated social change technologically and from a normative standpoint, and that such trends need to be analyzed in terms of their implications for the field of human rights.